"It just gives people hope": A qualitative inquiry into the lived experience of the Harry Potter world in mental health recovery. (July 2021) - Tribe, Kelsey V.; Papps, Fiona Ann; Calvert, Fiona
Highlights: Harry Potter fans shared how they used the series in their mental health recovery. Harry Potter fans described what is useful about the stories for this purpose. Fans engage with Harry Potter in spontaneous, informal, and creative ways. Therapeutic use of Harry Potter reflects current models of mental health recovery. Harry Potter seems uniquely suited to therapeutic use in mental health recovery. Abstract: The Harry Potter universe is both widely accessible and incredibly popular, and this feature combined with its depth of narrative and genre may make it uniquely suitable to supporting mental health recovery. The current study aims to address a gap in the literature around how engagement with the Harry Potter universe, in the tradition of unguided creative bibliotherapy, may allow people to derive psychologically-relevant meanings from these narratives as part of their mental health recovery journey. Semi-structured interviews were conducted with six individuals who identified as Harry Potter fans, had experienced mental health challenges, and were in recovery. Interviews were transcribed and analysed inductively to identify themes. Three superordinate themes were established that captured participants' experiences of using Harry Potter along their mental health recovery journey: Early Engagement, Immersive World, and Connection. Although participants employed Harry Potter in creative and individual ways, best suited to their lived experience of mental health recovery, the superordinate themes pointed to several commonalities in how these fans used the series, and these reflected contemporary models of mental health recovery.